Comparison of mandibular ramus and mental foramen among men and women: a study of panoramic radiographs in dental hospital of universitas gadjah mada - Salsabilla, Nadira; Widyaningrum, Rini; Diba, Silviana Farrah (Faculty of Dentistry, Universitas Islam Sultan Agung, 2022)
Background: The identification of victims is becoming an integral part of forensic investigations. The initial step in forensic identification is sex determination. Using panoramic radiographs, it is possible to determine the height of the mandibular ramus and the distance to the mental foramen for the purpose of sex determination. This study aimed to compare the mandible ramus height and mental foramen distance on panoramic radiographs between men and women.Method: This study utilized 70 panoramic radiographs of complete mandibular dentition from 35 men and 35 women aged 20 to 40 years. The samples were obtained from Dental Hospital of Universitas Gadjah Mada.Result: The average height of mandible ramus in male and female groups were 58.39±2.25 mm and 53.14±2.66 mm, respectively. The distance of the mental foramen was 12.68±1.63 mm in the male group and 10.83±1.23 mm in the female group. The Independent Sample t-test revealed that the p value for the difference between men and women in ramus height and mental foramen distance was 0.000 (p<0.05).Conclusion: Based on the result of this study, both the height of the mandible ramus and the distance of mental foramen on a panoramic radiograph differ significantly between males and females.